GUARDING THE DIGITAL CYBER REALM OF INDIA: NAVIGATING IPC 1860, BHARATIYA NYAYA SANHITA 2023 AND ITA 2000 IN THE FIGHT AGAINST CYBER CRIME - Meshram, Dr. Bandu B.; Singh, Manish Kumar (IJRDO Journal of Law and Cyber Crime, 2023)
The research paper explores critical aspects of cybercrime and the diagnostic & experimentation research for the applicability of IPC 1860/ BNS 2023 in cybercrimes using various cyber court judgements and Information Technology Act 2000 and its amendments. Most of the chapters of “Bharatiya Nyaya Sanhita 2023” are the mirroring chapters of IPC 1860 without straightforward applicability to cybercrimes or hacking or network communication digital crimes. While the IPC provisions are not specifically tailored to cybercrimes, but it can still be relevant in certain situations involving cybercrime. The provisions of BNS 2023 also apply to cyber crimes in India, However how? It is neither explicitly stated in IPC Nor in BNS. The researcher identifies probable IPC 1860 provisions which are also available in BNS 2023 for combating cybercrimes offences. Thus the research critically proves that the Indian Penal Code/ Bharatiya Nyaya Sanhita 2023” shall be adopted in the cybercrime justice systems. The legal interpretation and application of these provisions may vary case to case based on evolving legal standards and precedents.